Violence Against and Between Children Without Parental Care in Bosnia and Herzegovina - Muratbegović, Elmedin; Bulić, Dragana; Budimlić, Muhamed (Kriminalističke teme, 2017)
Reason for writing and research problem(s): Reason for writting and Researh problem(s): The seriousness of a modern state can certainly be measured today by the criteria of concern for children, but also by compelling attempts to protect children in all circumstances and statuses. The complexity of the problem of “violence against children” as a phenomenon undoubtedly points to the need for interdisciplinary action, but also for differentiated social responses. Specifically, we are talking about interventions undertaken by various institutions responsible for securing basic rights of the child, i.e interventions that depend on the form of violence, and the effectiveness of actions taken to protect children. Aims of the paper (scientific and/or social): The main objective of this paper is to get a clear picture of the scope and structure of violence against children and those in homes for children without parental care in BiH. Methodology/ Design: In this research, we have used specially developed data collection tools. Here, we primarily think of a questionnaire for children surveyed in homes for children without parental care but also for adults working in these homes. On the other hand, a special protocol for interviewing the focus group was developed for children in these homes. In the six focus groups, 69 children, girls and boys of school age participated in different vulnerable groups who are victims and / or witnesses of different forms of violence, abuse and neglect or are at risk of it. Focus groups were implemented at locations in Tuzla, Lukavac, and Sarajevo municipalities. Surveying was done using a set of questionnaires, developed specifically for each target category that addressed the following thematic groups of questions: Trust in the people around you; Violence in your environment; Violence Reporting System and Reaction to Violence. Research/ Paper limitation: Limitation of this study lies in the fact that we did not have access to homes in all parts of Bosnia and Herzegovina. Results/ General Conclusion: One fifth of surveyed children in the homes for children stated that the home can be place where one is victim to violence, because no one does anything to stop it, and the other half thinks that violence at the homes for children is not possible. On the other hand, the staff at the homes for children absolutely disagrees with this view. A very interesting fact concerns the view that the inside and outside of the children’s home is controlled by violent children, and nobody does anything to stop it, just over a third (34%) of surveyed children’s homes, agree with this fact, and of course the staff of children’s homes categorically rejects (84 %). Research/ Paper Validity: This research is to point out that we have to engage the investigations with “an open mind” and that we need to move away from interpreting statistical data from official institutions. This is particularly important in situations with problems regarding children. This work opens up the possibility of systematic action in the field of approximating the real state violence against children and among children in homes for children in Bosnia and Herzegovina.